Initial Evaluation of the Concept-2 Rowing Ergometer's Accuracy Using a Motorized Test Rig - Gunnar Treff; Gunnar Treff; Lennart Mentz; Benjamin Mayer; Kay Winkert; Thomas Engleder; Jürgen M. Steinacker (Frontiers Media S.A., 2022)
IntroductionThe Concept 2 (C2) rowing ergometer is used worldwide for home-based training, official competitions, and performance assessment in sports and science. Previous studies reported a disparate underestimation of mechanical power output positively related to an unclearly defined stroke variability. The aim of this study was to quantify the accuracy of the C2 while controlling for the potentially influencing variables of the rowing stroke by using a test rig for air-braked rowing ergometers and thus excluding biological variability.MethodsA unique motorized test rig for rowing ergometers was employed. Accuracy was assessed as the difference in mechanical power output between C2 and a reference system during steady (i.e., minimal variations of stroke power within a series of 50 spacemark, no -strokes) and unsteady simulated rowing (i.e., persistent variations during measurement series) while manipulating the stroke variables shape, force, or rate.ResultsDuring steady simulated rowing, differences between C2 and the reference system ranged 2.9-4.3%. Differences were not significantly affected by stroke shapes (P = 0.153), but by stroke rates ranging 22-28 min−1 (P < 0.001). During unsteady simulated rowing with alterations of stroke force and rate, mean differences of 2.5-3.9% were similar as during steady simulated rowing, but the random error increased up to 18-fold. C2 underestimated mechanical power output of the first five strokes by 10-70%. Their exclusion reduced mean differences to 0.2-1.9%.ConclusionDue to the enormous underestimation of the start strokes, the nominal accuracy of the C2 depends on the total number of strokes considered. It ranges 0.2-1.9%, once the flywheel has been sufficiently accelerated. Inaccuracy increases with uneven rowing, but the stroke shape has a marginal impact. Hence, rowers should row as even as possible and prefer higher stroke rates to optimize C2 readings. We recommend external reference systems for scientific and high-performance assessments, especially for short tests designs where the start strokes will have a major impact.